2009
DOI: 10.1007/s11740-009-0150-8
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve the geometric accuracy in asymmetric single point incremental forming

Abstract: Asymmetric incremental sheet forming (AISF) is a manufacturing process for the small batch production of sheet metal parts. In AISF, a sheet metal part is formed by a forming tool that moves under CNC control. AISF currently has two dominant process limits: sheet thinning and a limited geometric accuracy. This paper focuses on the latter limit. It is shown with a pyramidal part that multistage forming can yield an increased accuracy compared to single-stage forming. However, due to residual stresses induced du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(77 citation statements)
references
References 4 publications
0
64
0
1
Order By: Relevance
“…A characteristic of formative fabrication processes, particularly mouldless, freeform approaches, is that their positional accuracy is more highly dependent upon a combination of material behaviour and forming parameters than subtractive or additive approaches. Research into resultant incrementally formed geometries has shown significant deviations from the planned geometries (Bambach et al, 2009), and that parameters including the forming velocity, the toolpath, the size of material and distance to supports and particularly the material springback of the sheet during forming all affect the geometric accuracy of the resulting shape. These geometric deviations are a key deterrent from the widespread take-up of the process (Jeswiet et al, 2008).…”
Section: The Problem Of Accuracymentioning
confidence: 99%
“…A characteristic of formative fabrication processes, particularly mouldless, freeform approaches, is that their positional accuracy is more highly dependent upon a combination of material behaviour and forming parameters than subtractive or additive approaches. Research into resultant incrementally formed geometries has shown significant deviations from the planned geometries (Bambach et al, 2009), and that parameters including the forming velocity, the toolpath, the size of material and distance to supports and particularly the material springback of the sheet during forming all affect the geometric accuracy of the resulting shape. These geometric deviations are a key deterrent from the widespread take-up of the process (Jeswiet et al, 2008).…”
Section: The Problem Of Accuracymentioning
confidence: 99%
“…Without using dedicated dies, it uses a simple tool with a hemispherical end to form the sheet parts. By travelling along a 3D CAM toolpath on the surface of the sheet, the tool end deforms the sheet incrementally with the plastic deformation localised near the tool end [2] The simple dies are generally made of cheap materials like timber or resin [3] so that the cost in the fabrication and storage of dies is not huge. With the use of supporting dies, TPIF generally leads to better geometric accuracy of the formed parts than SPIF [4].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the poor geometric accuracy, some attempts have been presented in the literature, including experimental investigation of process parameters [4,6], hybrid ISF processes [7][8][9], the use of partially cut-out blanks [10], and a multi-stage strategy [3]. Recently, many studies concentrated on the toolpath correction/optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, incremental forming has been carried out on a wide range of materials including polymers [4][5], many of which have low forming limits, typically defined by a maximum wall angle at which no failure occurs. In addition, several efforts have been made to improve the accuracy of parts [6][7][8][9]. For instance, Verbert et al developed a feature based approach, where the behavior of individual features such as planes, ruled, freeform and ribs is taken into account to manufacture parts with high accuracy [7].…”
Section: Introductionmentioning
confidence: 99%